2002
DOI: 10.1152/japplphysiol.00367.2001
|View full text |Cite
|
Sign up to set email alerts
|

Plantar flexor activation capacity and H reflex in older adults: adaptations to strength training

Abstract: The purpose of this study was to investigate whether the voluntary neural drive and the excitability of the reflex arc could be modulated by training, even in old age. To this aim, the effects of a 16-wk strengthening program on plantar flexor voluntary activation (VA) and on the maximum Hoffman reflex (H(max))-to-maximum M wave (M(max)) ratio were investigated in 14 elderly men (65-80 yr). After training, isometric maximum voluntary contraction (MVC) increased by 18% (P < 0.05) and weight-lifting ability by 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
205
8
10

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(254 citation statements)
references
References 50 publications
31
205
8
10
Order By: Relevance
“…However, Porter et al (1995) question the generalization of such neural training effects across tasks. In addition, Scaglioni et al (2002) found increased voluntary activation of the plantar flexors in elderly after strength training but no increase in motor neuron excitability as evidenced by Hreflex amplitudes. It is therefore questionable whether the control of responses can be trained.…”
Section: Practical Implicationsmentioning
confidence: 85%
See 1 more Smart Citation
“…However, Porter et al (1995) question the generalization of such neural training effects across tasks. In addition, Scaglioni et al (2002) found increased voluntary activation of the plantar flexors in elderly after strength training but no increase in motor neuron excitability as evidenced by Hreflex amplitudes. It is therefore questionable whether the control of responses can be trained.…”
Section: Practical Implicationsmentioning
confidence: 85%
“…Motor neuron excitability appears reduced in the elderly, as evidenced by lower H-reflex amplitudes as compared to young adults (Scaglioni et al 2002). Pavol et al (2001) ascribed falls after tripping in a group of elderly subjects to a slower execution of the recovery strategy.…”
Section: Introductionmentioning
confidence: 99%
“…However, resistance training of the tibialis anterior was associated with a 32% increase in MEP amplitude produced by TMS during low-level contractions without changes in M-wave amplitude, indicating a role for spinal, corticospinal neurons, possibly M1 (25). In addition, several other studies showed that adaptations to acute and chronic voluntary and electrical stimulation-evoked muscle contractions, without a skill component, increased volitional drive from supraspinal centers (4, 13, 15, 24, 31, 32) without concomitant changes in H reflex, measured at rest or during mild voluntary contraction (1,10,13,15,23,24,35,38,50,55). However, the interpretation of these studies must be viewed carefully because they do not provide direct evidence for M1's involvement in strength gains and some studies did find increases in H reflex after resistance training (1,4,15,32).…”
Section: Role Of Primary Motor Cortex In Maximal Voluntary Forcementioning
confidence: 96%
“…Numerous studies have shown that the relationship is concave upward at medium forces and asymptotic at high voluntary forces [eg.1,18,28,29] . Some studies also indicate an upward convexity in the relationship at low voluntary forces [1,30] , although this is not always the case [15,26,31] .…”
Section: The Interpolated Twitch Ratiomentioning
confidence: 99%
“…It has been suggested that twitch interpolation involving a single superimposed stimulus may be incapable of detecting sub-optimal motor unit firing rates [42,43] and that the evoked-voluntary force relationship becomes less steep or even asymptotic at forces at which recruitment is complete and rated coding becomes the sole means of enhancing force [31] . This view is contradicted by two observations.…”
Section: The Interpolated Twitch Ratiomentioning
confidence: 99%